Cultural and Professional Trends towards Psychological and Educational Counseling as Perceived by Psychology Students at Hebron University - Makahmreh, Kamal Kahlil (Journal of Educational and Psychological Sciences, 2022)
This study aimed at identifying the cultural and professional trends towards psychological and educational counseling as perceived by psychology students at Hebron University. It also aimed at recognizing the effect of each of the variables (academic level, GPA, father’s education level, and mother’s education level) on their cultural and professional attitudes. The study population consisted of 118 students specialized in psychological and educational counseling. The study was conducted on a stratified random sample of (59) teachers forming 50% of the study population. The researcher used the questionnaire of cultural and professional trends. Results of the study showed that cultural and professional trends towards psychological and educational counseling as perceived by psychology students at the University of Hebron came with a medium degree (neutral), with no statistically significant differences in the estimates of the subjects of the study attributed to the variables (academic level, GPA, father education level, and the level of Mother's education).
Keywords: Cultural Orientation; Professional Orientation; Psychological and Educational Counseling